God, grace, and righteousness in Wisdom of Solomon and Paul's letter to the Romans : texts in conversation - Linebaugh, Jonathan A. (Novum Testamentum, Supplements, 2013)
In God, Grace, and Righteousness in Wisdom of Solomon and Paul's Letter to the Romans , Jonathan A. Linebaugh places the Wisdom of Solomon and the Letter to the Romans in conversation. Both texts discuss the relationship of Jew and Gentile, the meaning of God's grace and righteousness, and offer readings of Israel's scripture. These shared themes provide talking-points, initiating a dialogue on anthropology, soteriology, and hermeneutics. By listening in on this conversation, Linebaugh demonstrates that while these texts have much in common, the theologies they articulate are ultimately incommensurable because they think from different events - Wisdom from the pre-creational order crafted by Sophia and exemplified in the Exodus; Paul from the incongruous gift of Christ which justifies the ungodly.